2012
DOI: 10.1073/pnas.1209166109
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the leading process, nucleus, and Golgi apparatus of migrating cortical interneurons in living mouse embryos

Abstract: Precisely arranged cytoarchitectures such as layers and nuclei depend on neuronal migration, of which many in vitro studies have revealed the mode and underlying mechanisms. However, how neuronal migration is achieved in vivo remains unknown. Here we established an imaging system that allows direct visualization of cortical interneuron migration in living mouse embryos. We found that during nucleokinesis, translocation of the Golgi apparatus either precedes or occurs in parallel to that of the nucleus, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 44 publications
(74 reference statements)
6
60
0
Order By: Relevance
“…At P0, our results show that CLASP2 knockdown caused a reduction in the distance between the nucleus and centrosome when compared to controls (Figure 6A). Similar to previous reports, we found co-localization of Golgi and centrosome markers in both control and CLASP2 shRNA electroporated cells (Yanagida et al, 2012). The Golgi and centrosome complex was localized to the leading process in ~80% of GFP-positive control cells; however, following CLASP2 knockdown, there was a mislocalization of this complex with a higher percentage of cells with Golgi and centrosome staining adjacent to the nucleus (Figure 6B and 6C).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…At P0, our results show that CLASP2 knockdown caused a reduction in the distance between the nucleus and centrosome when compared to controls (Figure 6A). Similar to previous reports, we found co-localization of Golgi and centrosome markers in both control and CLASP2 shRNA electroporated cells (Yanagida et al, 2012). The Golgi and centrosome complex was localized to the leading process in ~80% of GFP-positive control cells; however, following CLASP2 knockdown, there was a mislocalization of this complex with a higher percentage of cells with Golgi and centrosome staining adjacent to the nucleus (Figure 6B and 6C).…”
Section: Resultssupporting
confidence: 92%
“…The positioning of the centrosome and Golgi apparatus is a key step in selecting migratory direction, and their translocation into the leading neurite precedes cell movement during neuronal migration (Yanagida et al, 2012; Sakakibara et al, 2013). Because CLASP2 is enriched at both the Golgi and centrosome, two organelles that control cell polarity (Miller et al, 2009; Beffert et al, 2012), we examined whether CLASP2 expression influenced the position and shape of the centrosome/Golgi complex during neuronal migration.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, cytoplasm elongation was often observed preceding nucleokinesis (Figure 7G). These behaviors are remarkably similar to previous reports of interneuron migration in live mouse embryos, mouse MGE explant models, and postmortem human brain sections (Bellion et al, 2005; Ma et al, 2013; Paredes et al, 2016; Yanagida et al, 2012), demonstrating the suitability of using hfMCOs to study human interneuron migration.…”
Section: Resultssupporting
confidence: 88%
“…We found that soma translocation of interneuron progenitors was dramatically decreased with 50 μM blebbistatin treatment (10.55 ± 2.25%, n=2 hfMCOs, 63 cells in total, mean ± SD) compared with control hfMCOs (41.23 ± 3.20%, n=4 hfMCOs, 79 cells in total, mean ± SD) within 10 hours, and 100 μM blebbistatin treatment completely abolished migration (n=2 hfMCOs, 44 cells in total, mean ± SD) (Figure 7H and 7I; Movie S5 and S6). The average migrating speed of interneuron progenitors was 0.19 ± 0.01 μm/min (n=35 cells from 4 hfMCOs, mean ± SD) (Figure 7J), which was close to the speed observed from living embryo but slower than that obtained from MGE explant culture (Bellion et al, 2005; Yanagida et al, 2012), indicating that the cellular environment of hfMCOs might closely approximate their in vivo counterparts. With myosin II inhibition, the migration speed largely decreased (Figure 7J).…”
Section: Resultssupporting
confidence: 71%
“…Co-electroporation of Cre-IRES-GFP, together with a vector containing Bcl11a-XL cDNA, was sufficient to completely normalize the ratio of multi-to bipolar morphologies ( Figures 3A-3C). To further characterize polarization in Bcl11a mutant cortical neurons, we labeled the Golgi apparatus with GFP-tagged galactosyltransferase (Jossin and Cooper, 2011;Yanagida et al, 2012) and quantified the proportion of Bcl11a mutant and control cells with the Golgi apparatus facing the CP ( Figure 3D). Loss of Bcl11a resulted in a significant decrease of cells with a radially oriented Golgi apparatus already at E16.5 ( Figures 3D and 3E), supporting a role of Bcl11a in cortical neuron polarization.…”
Section: Bcl11a Controls Bipolar Morphology Of Migrating Neuronsmentioning
confidence: 99%